Host preferences, colour patterns and distribution records of pseudocryptochirus viridis hiro, 1938 (Decapoda, Cryptochiridae) - Van Der Meij, S (Brill Academic Publishers, 2012)
The coral gall crab Pseudocryptochirus viridis is an obligate symbiont of some species of the Indo-West Pacific coral genus Turbinaria. The colour pattern variation within the species is illustrated for the first time. Overviews of the coral host species and distribution records are provided, including new records from Indonesia, Malaysia and Australia.